Hadith #221 - Sunan al-Nasa'i - Aisha bint Abi Bakr; Hisham bin 'Urwa هشام بن عروة; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني; Urwa ibn al-Zubayr عروة بن الزبير (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) said: ‘None of you should perform Ghusl in standing water when he is Junub.'”
Grade:

Hadith #367 - Sunan al-Nasa'i - Aisha bint Abi Bakr; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني (Sunan al-Nasa'i)
“O Messenger of Allah, I do not become pure, so should I stop praying? He said: “no, that is a vein.” – (One of the narrators) Khalid said, in what I read from him – “and it is not menstruation, so when your period comes, stop praying, and when it goes, wash the blood from yourself and pray.”
Grade:

Hadith #754 - Sunan al-Nasa'i - al-Hakam bin 'Utayba الحكم بن عتيبة; ibn Abbas; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Suhayb bin Sinan ar-Rumi; Yahya bin al-Jazar al-Arni يحيى بن الجزار (Sunan al-Nasa'i)
“Al-Fadl and I came riding a female donkey of ours, and the Messenger of Allah(ﷺ) was leading the people at Arafat.” Then he said something to that effect. “We passed by part of the row, and then we dismounted and left the donkey grazing, and the Messenger of Allah(ﷺ)did not say anything to us.”
Grade:

Hadith #1237 - Sunan al-Nasa'i - Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; Imran bin Husain; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني; Yazid bin Zari' يزيد بن زريع (Sunan al-Nasa'i)
The Prophet (ﷺ) prostrated after the salam when he was not sure.
Grade:

Hadith #1657 - Sunan al-Nasa'i - Abdullah bin Shaqayq al-Aqayli عبد الله بن شقيق العقيلي; Sa'id bin Iyas al-Jariri سعيد بن إياس الجريري; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني; Yazid bin Zari' يزيد بن زريع (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) did not refrain from (kissing) my forehead when he was fasting, and he did not die until most of his prayers were offered sitting down.” Then she said something to the effect that (referred to the prayers) other than the obligatory prayers. “And the dearest of actions to him was that in which a person persists, even if it is little.”
Grade:

Hadith #1837 - Sunan al-Nasa'i - Anas ibn Malik; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Qatada قتادة; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي; Ubada bin As-Samit (Sunan al-Nasa'i)
“A man who had been born in Al-Madinah died there, and the Messenger of Allah prayed for him, then he said: ‘Would that he had died somewhere other than the place where he was born.’ They said: ‘Why is that, O Messenger of Allah?’ He said: If a man dies somewhere other than the place where he was born, a space in him equal to the distance between the place where he was born and the place where he died.”
Grade:

Hadith #2157 - Sunan al-Nasa'i - Anas ibn Malik; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Qatada قتادة; Sa'id bin Abi Sa'id; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني (Sunan al-Nasa'i)
“We said to Hudhaifah: ‘At what time did you take Sahur with the Messenger of Allah?’ He said: ‘It was daytime, but before the sun had risen.” (Daif)
Grade:

Hadith #2185 - Sunan al-Nasa'i - Abdullah bin Shaqayq al-Aqayli عبد الله بن شقيق العقيلي; Sa'id bin Iyas al-Jariri سعيد بن إياس الجريري; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني; Yazid bin Zari' يزيد بن زريع (Sunan al-Nasa'i)
“The Messenger of Allah did not fast in any month of the year more than he did in Shaban. He used to fast all of Shaban.”
Grade:

Hadith #2676 - Sunan al-Nasa'i - Ayoub al-Sakhtiyani أيوب السختياني; ibn Umar; Nafie' نافع مولى ابن عمر; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني; Yazid bin Zari' يزيد بن زريع (Sunan al-Nasa'i)
‘Pants (are allowed) for one who cannot find an Izar, and Khuffs for one who cannot find sandals to wear in Ihram.;;
Grade:

Hadith #3276 - Sunan al-Nasa'i - Aban bin 'Uthman أبان بن عثمان بن عفان; Nubiya bin Wahb bin 'Uthman نبيه بن وهب بن عثمان; Sa'id bin Abi Sa'id; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني; Uthman ibn 'Affaan; Y'la bin Hkym al-Thqfy يعلى بن حكيم الثقفي; Yazid bin Zari' يزيد بن زريع (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘An orphan girl should be consulted with regard to marriage, and if she remains silent, that is her permission. If she refuses then she is not to be forced.'”
Grade:

Hadith #3697 - Sunan al-Nasa'i - ibn Abbas; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Qatada قتادة; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘No one should take back his gift except a father (taking back a gift) from his son. The one who takes back his gift is like one who goes back to his vomit.'”
Grade:

Hadith #4412 - Sunan al-Nasa'i - Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; al-Husain bin Hryth الحسين بن حريث; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Shadad bin Aus bin Thabit; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني (Sunan al-Nasa'i)
“A man form among the Ansar had a she-camel which used to graze in front of Uhud. Something happened to it, and he slaughtered it with a stake,”- (Ayyub, one of the narrators, said) I said to Zaid:’ A stake of wood or of iron?” He said “No of wood.”- “Then he went to the Prophet and asked him, and he told him to eat it.” (Sahih )
Grade:

Hadith #4464 - Sunan al-Nasa'i - Abdullah ibn al-Harith ibn Nawfal; Hakim ibn Hizam; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Qatada قتادة; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘There will come a time when a man will not care where his wealth comes from, whether (the source is) Halal or Haram.”
Grade:

Hadith #4563 - Sunan al-Nasa'i - Abdah bin Sulaiman al-Klabi عبدة بن سليمان الكلابي أبو محمد الكوفي; Muslim bin Yasar al-'Abbassri مسلم بن يسار البصري - مسلم سكرة المصبح; Qatada قتادة; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني; Ubada bin As-Samit (Sunan al-Nasa'i)
the Messenger of Allah appointed a man in charge of kharibar and he brought some Janib dates. The messenger of Allah said; “Are all the dates if khaibar like this?” He said: “No (by Allah, O Messenger of Allah) we take a Sa of these for two for three Sas (of other types of dates).” The messenger of Allah said: “do not do that Sell the mixed dates for Dirhams then buy the Janib dates with the Dirhams” ,”
Grade:

Hadith #4564 - Sunan al-Nasa'i - Amr bin 'Asim al-Kalabi عمرو بن عاصم الكلابي; Hamam bin Munabbih همام بن منبه بن كامل; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Muslim bin Yasar al-'Abbassri مسلم بن يسار البصري - مسلم سكرة المصبح; Qatada قتادة; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني; Ubada bin As-Samit; Ya'qub bin Ibrahim bin Sa'd يعقوب بن إبراهيم بن سعد بن إبراهيم (Sunan al-Nasa'i)
some dates from trees that were irrigated artificially were brought to the Messenger of Allah and the dates of the messenger of Allah were dates from trees that were nourished by their roots. He said: “Where did you get these from?” They said: “We bought a Sa of them for two Sa s of our dates: He said: “Do not do that, for this is not right. Rather sell your dates and but what you need of these,”
Grade:

Hadith #4843 - Sunan al-Nasa'i - Abu Musa al-Asha'ari; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Qatada قتادة; Sa'id bin Abi Sa'id; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني (Sunan al-Nasa'i)
“some people from Banu Tha’labah came to the Prophet when he was delivering a speech and a man said; “O Messenger of Allah, these are Banu Tha’labah bin Yarbu’ who killed so and so’ – one of the Companions of the Prophet The Prophet said: “No soul is affected by the sin of another.
Grade:

Hadith #5027 - Sunan al-Nasa'i - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
‘Ali said: “The Unlettered Prophet made a covenant with me, that none but a believer would love me, and none but a hypocrite would hate me.”
Grade:

Hadith #3348 - Sunan Abi Dawud - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; Muslim bin Yasar al-'Abbassri مسلم بن يسار البصري - مسلم سكرة المصبح; Qatada قتادة; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني; Ubada bin As-Samit (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: Gold for gold is interest unless both hand over on the spot ; wheat for wheat is interest unless both hand over on the spot ; dates for dates is interest unless both hand over on the spot ; barley for barley is interest unless both hand over on the spot.
Grade: Sahih

Hadith #3349 - Sunan Abi Dawud - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubada bin As-Samit; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: Gold is to be paid for with gold, raw and coined, silver with silver, raw and coined (in equal weight), wheat with wheat in equal measure, barley with barley in equal measure, dates with dates in equal measure, salt by salt with equal measure; if anyone gives more or asks more, he has dealt in usury. But there is no harm in selling gold for silver and silver (for gold), in unequal weight, payment being made on the spot. Do not sell them if they are to be paid f
Grade: Sahih

Hadith #496 - Jami' al-Tirmidhi - Abdullah bin 'Isa bin 'Abdur Rahman عبد الله بن عيسى بن عبد الرحمن; Mahmud bin Ghaylan محمود بن غيلان العدوي مولاهم أبو أحمد; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Waki' bin al-Jarrah وكيع بن الجراح; Yahya bin al-Harith al-Dhamari يحيى بن الحارث الذماري (Jami' al-Tirmidhi)
“Allah’s Messenger said to me: ‘Whoever performs Ghusl on Friday, and bathes completely, and goes early, arriving early, gets close and listens and is silent, there will be for him in every step he take the reward of a year of fasting and standing (in prayer).'”
Grade:

Hadith #1395 - Jami' al-Tirmidhi - Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; Ahmed bin Manay' أحمد بن منيع; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Shadad bin Aus bin Thabit; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني (Jami' al-Tirmidhi)
that the Prophet (ﷺ) said: “The world ceases to exist is less significant to Allah than killing a Muslim man.”
Grade:

Hadith #1138 - Sunan Ibn Majah - Abdur Rahman bin Yazid bin Jabir عبد الرحمن بن يزيد بن جابر الأزدي; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; al-Husain bin 'Ali bin al-Walid al-Ja'fi الحسين بن علي بن الوليد الجعفي; Shadad bin Aus bin Thabit; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني (Sunan Ibn Majah)
“One prayer in this mosque of mine is better than a thousand prayers anywhere else, except The Sacred Mosque (Al-Masjid Al-Haram).” (Another chain) from Abu Hurairah from the Prophet (ﷺ) with similar wording.
Grade:

Hadith #1140 - Sunan Ibn Majah - Abdullah bin Mubarak عبد الله بن المبارك; Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Hsan bin Atyh al-Mharby حسان بن عطية المحاربي مولاهم; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني (Sunan Ibn Majah)
“One prayer in my mosque is better than one thousand prayers elsewhere, except the Sacred Mosque, and one prayer in the Sacred Mosque is better than one hundred thousand prayers elsewhere.”
Grade:

Hadith #1705 - Sunan Ibn Majah - Abdur Rahman bin Yazid bin Jabir عبد الرحمن بن يزيد بن جابر الأزدي; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; al-Husain bin 'Ali bin al-Walid al-Ja'fi الحسين بن علي بن الوليد الجعفي; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني (Sunan Ibn Majah)
“The Messenger of Allah used to divide his time equally among his wives, then he would say ‘O Allah, this is what I am doing with regard to that which is within my control, so do not hold me accountable for that which is under Your control and is beyond my control.'”
Grade: